Convergence of Row Sequences of Simultaneous Padé-orthogonal Approximants - N. Bosuwan (2018)
© 2017, Springer-Verlag Berlin Heidelberg. In this paper, convergence theorems of row sequences of vector valued Padé-orthogonal approximants (simultaneous Padé-orthogonal approximants) corresponding to a measure supported on a general compact subset of the complex plane are proved. These theorems are natural extensions of Montessus de Ballore’s theorem for row sequences of (scalar) Padé-orthogonal approximants in Bosuwan et al. (Jaen J Approx 5:179–208, 2013).